A Note on Very Weak Solutions for a Class of Nonlinear Elliptic Equations - Juling, Li; Hongya, Gao (Sarajevo Journal of Mathematics, 2024)
We prove a new a priori estimate for very weak solutions of a class of nonlinear elliptic equations. 2000 Mathematics Subject Classification. 30C62, 35J60